Trade Credit and Performance of Food Production Companies in Vietnam - An, Pham Thi Ha (International Journal of Management and Sustainability, 2021)
Trade credit (TR) plays an important role in financial structure and impacts on company performance. The issues related to TR have long been researched, with the first studies conducted by Nadiri (1969); Schwartz (1974); Lewellen, McConnell, and Scott (1980); Ferris (1981); Emery (1984). This study applies panel regression models, such as Pooled OLS, Fixed Effects, Random Effects, and FGLS, to evaluate the impact of TR on the performance of Food Production Companies in Vietnam. Company performance is measured by the Data Envelopment Analysis model (DEA). In addition, the Bayesian analysis method is used to test the robustness of the estimators from the models evaluating the effect of TR on company performance. Using annual data from the financial statements of 35 Vietnamese Food Production companies in the period 2008-2020, provided by Thomson Reuters, the results reveal a non-linear relationship between TR and company performance with an inverted U shape. Specifically, when TR, or accounts receivable on total assets, increases, company performance will also increase. However, when the increase in accounts receivable on total assets exceeds a certain limit, company performance will decrease. Based on the results, some policy implications are suggested to manage the accounts receivables effectively in Vietnamese Food Production Companies.